2010
DOI: 10.3109/10253891003667870
|View full text |Cite
|
Sign up to set email alerts
|

Immune–metabolic balance in stressed rats duringCandida albicansinfection

Abstract: We evaluated the host metabolic response to chronic varied stress during infection with the fungus Candida albicans. We used four groups of female Wistar rats: normal uninfected and unstressed, stressed, C. albicans infected and infected, and stressed. Infected rats reacted with rapid metabolic adjustments, evident as anorexia and body weight loss, partly mediated by glucocorticoids and TNF-alpha. Higher circulating levels of IL-6 and glucose (p < 0.05) revealed the progress and catabolic effect of the inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…In our data, one might infer that the positive correlation between CRP and body weight would represent a higher amount of fetal adipose tissue, or a more active adipose tissue, since many times the higher body weight in children with FIRS can be justified by edema caused by an inflammatory process in the face of aggressive agents [34]. TNF- α in inflammatory condition may be involved in alterations of the body weight through the association of the TNF- α with glucocorticoids as well as in promoting resistance to insulin [35]. Therefore, to complement the idea that the reduction of body weight is the first sign of intrauterine stress [36], we understand that the severe stress observed in our cases may have been responsible for the development of other alterations such as FIRS and also edema or lipid accumulation, resulting in the increase of body weight through different mechanisms [37].…”
Section: Discussionmentioning
confidence: 99%
“…In our data, one might infer that the positive correlation between CRP and body weight would represent a higher amount of fetal adipose tissue, or a more active adipose tissue, since many times the higher body weight in children with FIRS can be justified by edema caused by an inflammatory process in the face of aggressive agents [34]. TNF- α in inflammatory condition may be involved in alterations of the body weight through the association of the TNF- α with glucocorticoids as well as in promoting resistance to insulin [35]. Therefore, to complement the idea that the reduction of body weight is the first sign of intrauterine stress [36], we understand that the severe stress observed in our cases may have been responsible for the development of other alterations such as FIRS and also edema or lipid accumulation, resulting in the increase of body weight through different mechanisms [37].…”
Section: Discussionmentioning
confidence: 99%
“…C. albicans is implicated in mucocutaneous infections such as oral, anorectal and vaginal candidiasis 12–14 . It is also an important agent of serious systemic infections of immuno‐compromised patients 9–11,15 . Infections caused by M. pachydermatis or C. albicans have a chronic character, and are characterised by a high percentage of relapses 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Leptin receptor-deficient obese ( fa/fa ) rats show impaired host defense against C. albicans infection whereas, in stressed rats this infection caused a prompt reduction in systemic leptin levels and increased TNF-α levels (Rodríguez-Galán et al, 2010 ). However, it has been suggested that the leptin can activate healing the critical illness in stress-related activities (Bornstein et al, 1998 ).…”
Section: Fate Of Leptin In Microbial Infectionsmentioning
confidence: 99%